Особливості морфологічної будови вегетативної сфери Camellia sasanqua Thunb. - Kharchenko, I.I. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2015)
The results of studies of morphological structure of the vegetative organs of Camellia sasanqua Thunb. under glasshouse conditions are provided. The characteristic features of vegetative organs C. sasanqua are identified. The peculiarities of morphological structure of the leaf are described in detail. The loss of strongly pronounced terminal series of the leaves in C. sasanqua was revealed. The variability of the leaf blade form both between various individuals of the same species and within the single plant was detected. The heterophyly pattern in the form of doubled leaf apex was revealed. The presence of transitional leaf form from the lower leaf series to the middle one was established. A significant similarity of the morphological structure of vegetative organs of C. sasanqua and C. japonica L. was revealed. Significant differences between these species comprise just in both the dimensions and the form of vegetative organs.